Leveraging National Cancer Institute Programmatic Collaboration for Uterine Cervix Cancer Patient Accrual in Puerto Rico - Kunos, Charles A.; Massett, Holly A.; Galassi, Annette; Walker, Joan L.; Good, Marge J.; Díaz, Luis Báez; McCaskill-Stevens, Worta (Frontiers in Oncology, 2018)
Women in the U.S. Commonwealth of Puerto Rico (PR) have a higher age-adjusted incidence rate for uterine cervix cancer than the U.S. mainland as well as substantial access and economic barriers to cancer care. The National Cancer Institute (NCI) funds a Minority/Underserved NCI Community Oncology Research Program in PR (PRNCORP) as part of a national network of community-based healthcare systems to conduct multisite cancer clinical trials in diverse populations. Participation by the PRNCORP in NCI’s uterine cervix cancer clinical trials, however, has remained limited. This paper reports on the findings of a NCI site visit in PR to assess barriers impeding site activation and accrual to its sponsored gynecologic cancer clinical trials. Qualitative, semi-structured individual and group interviews were conducted at six PRNCORP-affiliated locations to ascertain: long-term trial accrual objectives; key stakeholders in PR that address uterine cervix cancer care; key challenges or barriers to activating and to enrolling patients in NCI uterine cervix cancer treatment trials; and resources, policies, or procedures in place or needed on the island to support NCI-sponsored clinical trials. A NCI-sponsored uterine cervix cancer radiation-chemotherapy intervention clinical trial (NCT02466971), already activated on the island, served as a test case to identify relevant patient accrual and site barriers. The site visit identified five key barriers to accrual: (1) Lack of central personnel to coordinate referrals for treatment plans, medical tests, and medical imaging across the island’s clinical trial access points; (2) Patient insurance coverage; (3) Lack of a coordinated brachytherapy schedule at San Juan-centric service providers; (4) Limited credentialed radiotherapy machines island-wide; and, (5) Too few radiology medical physicists tasked to credential trial-specified positron emission tomography scanners island-wide. Puerto Rico offers a unique opportunity to study overarching and tactical strategies for improving accrual to NCI-sponsored gynecologic cancer clinical trials. Interview findings support adding and re-tasking personnel for coordinated trial-eligible patient referral, accrual, and treatment.